Three novel iridium (III) complexes containing double chiral atoms for organic light‐emitting diodes - Gan Cheng; Jun‐jian Lu; Li‐Ya Zhu; Guangzhao Lu (Micro & Nano Letters, 2023)
Abstract Chiral iridium (III) complexes are very important for the preparation of circularly polarized organic diodes light‐emitting diodes (CP‐OLEDs). Three novel iridium (III) complexes, Ir(dnfppy)2(Cl/pyrrole), Ir(dfppy)2(dpp), and Ir(tfmqz)2(sdpp), have been synthesized and characterized, respectively. These iridium (III) complexes emitted deep‐blue, blue, and red photoluminescence with high quantum yields (Ir(dnfppy)2(Cl/Pyrrole): λmax = 447 nm, F = 62.4%; Ir(dfppy)2(dpp): λmax = 467 nm, F = 25%; Ir(tfmqz)2(sdpp): λmax = 609 nm, F = 73.7%). Compared with Ir(dnfppy)2(Cl/pyrrole), the HOMO energy levels of Ir(dfppy)2(dpp) and Ir(tfmqz)2(sdpp) were calculated to be −5.71/−5.73 eV, and the LUMO energy levels were increased to be −2.75/−3.36 eV, respectively. The circular dichroism spectra of two pairs of the enantiomers for Ir(dfppy)2(dpp) or Ir(tfmqz)2(sdpp) displayed symmetry with opposite polarization between 300 and 600 nm. The maximum external quantum efficiency (EQEmax) of OLEDs based on Ir(tfmpqz)2(sddp) was 13.8%, showing a relatively low efficiency roll‐off with the EQE of 10.7% at 5000 cd/m2.